2016
DOI: 10.3390/ijgi5010005
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Analysis on Contribution Inequality in OpenStreetMap: A Comparative Study for Four Countries

Abstract: Contribution inequality widely exists in OpenStreetMap (OSM), which means that most data come from a minority of the contributors, while the majority only accounts for a small percentage of data. This phenomenon is of great importance to understanding from where the data come and how the project evolves. The investigation in this paper is dedicated to answering the following questions: How does contribution inequality change over time in OSM? Which group of contributors plays a more important role in influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Since Mapillary images include information about time and geographic coordinates, social and physical behavior of humans can be studied on a worldwide scale through an examination of user contribution patterns [3]. Similar to other VGI data, user contribution patterns and the data accumulation process are the fundamental differences between Mapillary and traditional street view data platforms [4], and these analyses can provide a basis for answering questions about the quantity, quality, and type of Mapillary data [5,6]. Walden-Schreiner et al [7] used Flickr photos to assess seasonal patterns of visitor use in protected mountain areas, providing a basis for the effective management of protected areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Mapillary images include information about time and geographic coordinates, social and physical behavior of humans can be studied on a worldwide scale through an examination of user contribution patterns [3]. Similar to other VGI data, user contribution patterns and the data accumulation process are the fundamental differences between Mapillary and traditional street view data platforms [4], and these analyses can provide a basis for answering questions about the quantity, quality, and type of Mapillary data [5,6]. Walden-Schreiner et al [7] used Flickr photos to assess seasonal patterns of visitor use in protected mountain areas, providing a basis for the effective management of protected areas.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, knowing about the user's contribution patterns (walking, cycling, and driving) and the equipment used for contribution can give us a more targeted understanding of the data composition of Mapillary. Contribution inequality has substantial and complicated impacts on data quality and on the developments of the project [4]. We expect the emergence of a small set of users who do most of the work in the Mapillary community.…”
Section: Introductionmentioning
confidence: 99%
“…Many comparative studies have shown that crowdsourced geographic information can be as good, if not better, than data from authoritative sources [58,59]. A comprehensive literature overview of the latest developments in crowdsourced geographic information research is presented in Reference [60], with a focus on trends related to OpenStreetMap while many others have discussed the quality of this volunteer data source [61][62][63]. Of the topics selected by the authors for future research, they emphasize the areas of: Intrinsic data quality assessment, conflation methods which combine crowdsourced geographic information and other data sources, and the development of credibility, reputation, and trust methodologies for crowdsourced geographic information.…”
Section: Quality and Use Of The Data For Researchmentioning
confidence: 99%
“…Open-source software, as a method for data collection and gaining knowledge, is increasingly becoming important within the field of natural hazards (Eckle et al, 2016;Klonner et al, 2016). For instance, OpenStreetMap (OSM) and other voluntary geographic information services help to create comprehensive databases of up-to-date geospatial data which also can be used for natural risk assessment (Schelhorn et al, 2014;Vaz and Arsanjani, 2015;Yang et al, 2016).…”
Section: Contents Of the Surveymentioning
confidence: 99%